Hubungan Antara Kadar Lemak, Status Gizi dan VO2max Pada Atlet Cabang Olahraga Bola Basket di Club Amores Karawang Provinsi Jawa Barat - Wijaya, Habibi Hadi; Nurhadi, Maha Dewi Afifah; Rizky, Muhammad; Sentana, Bima; Alkautsar, Fata Azima (Institut Teknologi Bandung, 2024)
The relationship between body fat percentage, Body Mass Index (BMI), and Volume of Maximal Oxygen (VO2max) is critical to understanding athlete health and performance. BMI and body fat content are important metrics that indicate athletes' body composition, while VO2max indicates their aerobic capacity. Therefore, careful research and monitoring of all three components is essential to create the most effective training methods to help athletes reach their full potential. This research uses a quantitative approach, and the type is descriptive correlation. That is, the purpose of this study is to determine whether or not there is a relationship between certain variables, in this case nutritional status and VO2max of basketball athletes of Club Amores Karawang. The study involved 37 teams of middle and high school students aged between 12 and 16 years old. Among the samples taken, 13 (12.63%) were female athletes and 24 (23.63%) were male athletes. The comparison of educational levels started in junior high school grade 7 with 10 (9.63%) samples, junior high school grade 8 with 7 (6.63%) samples, junior high school grade 9 with 12 (11.63%) samples, senior high school grade 10 with 6 (5.63%) samples, and high school grade 11 and 12 samples totaled 1 (1.26%) each, and the sample of athletes aged 12 years totaled 6 (5.63%), 13 years totaled 7 (6.63%), 14 years totaled 11 (10.63%), 15 years totaled 8 (7.63), and 16 years totaled 5 (4.63%). Therefore, it is imperative to understand the complex relationship between BMI, body fat content, and VO2max when creating training programs intended to support the optimal health and performance of basketball athletes.